Respiratory distress syndrome in preterm neonates in the era of precision medicine: A modern critical care-based approach - Daniele De Luca (Elsevier, 2021)
Respiratory distress syndrome (RDS) was recognized to be caused by primary surfactant deficiency almost 70 years ago and continuous positive airway pressure was introduced approximately 50 years ago. Since then, there have been many developments in neonatology; we know many things but others are still controversial. The more we know, the more questions arise. However, this review aims to indicate what is more needed to understand and how should be the modern approach to RDS in the era of precision medicine. The review is divided between new concepts and new tools. We will explain the interaction between steroids, CPAP and surfactant, as well as the surfactant catabolism and the diagnosis of NARDS; lung ultrasound and new tools to optimize CPAP will also be covered. How these concepts are integrated in the author's personal experience is also illustrated.